Study on Enhancing Zinc Dusts with Direct Sulphuric Acid Leaching - Sun, H.Y.; Kong, X.; Sen, W.; Liu, G.Y. (Asian Journal of Chemistry, 2015)
The mechanical activation of zinc dusts to enhance leaching of zinc and lead going into leaching residue with direct sulphuric acid leaching have been performed in the paper. Some technical parameters were mainly investigated and optimized, including concentration of initial acid, liquid-solid ratio, leaching time and leaching temperature. The SEM measurement and DTA-TG analysis were conducted to check the change of microstructure and thermodynamics stability of zinc dusts before and after mechanical activation for 0.5 h. It was found that before mechanical activation the optimum technical conditions were concentration of H2SO4 175 g/L, liquid-solid ratio 7:1, leaching temperature 80 °C, leaching time 60 min and leaching rate of zinc was 92.47 % and rate of lead going into leaching residue was 90.83 %. After 0.5 h milling, the optimum technical parameters were concentration of H2SO4 150 g/L, liquid-solid ratio 5:1, leaching temperature 50 °C, the leaching time 40 min and leaching rate of zinc was 91.52 % and rate of lead going into leaching residue was 95.36 %.